2010
DOI: 10.1167/iovs.10-5316
|View full text |Cite
|
Sign up to set email alerts
|

17-β Estradiol Protects ARPE-19 Cells from Oxidative Stress through Estrogen Receptor-β

Abstract: These results indicate that 17β-E(2) protects ARPE-19 cells from oxidative stress through an ERβ-dependent mechanism. 17β-E(2)-mediated cytoprotection occurred through the preservation of mitochondrial function, reduction of ROS production, and induction of cellular antioxidant genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 34 publications
10
53
0
Order By: Relevance
“…According to these data, E2:ERb complex-mediated cytoprotection from oxidative stress has been reported also in ARPE cells (Giddabasappa et al 2010). As a consequence, our data strongly support that Nar-mediated skeletal muscle protection from ROS-induced oxidative stress depends on its ERb agonist activity rather than a free radical quenching compound activity.…”
Section: Discussionsupporting
confidence: 86%
“…According to these data, E2:ERb complex-mediated cytoprotection from oxidative stress has been reported also in ARPE cells (Giddabasappa et al 2010). As a consequence, our data strongly support that Nar-mediated skeletal muscle protection from ROS-induced oxidative stress depends on its ERb agonist activity rather than a free radical quenching compound activity.…”
Section: Discussionsupporting
confidence: 86%
“…Both ERa and ERb have been identified in human retina. 18,19 In fact, Ogueta and colleagues in 1999 found that ERa concentrations decreased with age (35 > 49 > 74 years) in women, whereas males had ERa levels that were between those of 49-and 74-year-old women. 20 In addition, some studies do report a difference in the occurrence of PDR, which can be attributed to puberty.…”
mentioning
confidence: 99%
“…Estrogen receptors have been found in the human RPE, and estrogen provides an antioxidant effect by inhibiting lipid peroxidation. Related studies revealed that patients exposed to estrogen due to hormone replacement therapy or pregnancy had increased incidence of AMD (18)(19)(20)(21)(22). Pathogenesis of AMD is multifactorial and choroidal thickness might be playing a role in this broad pathogenetic cycle of the disease.…”
Section: Discussionmentioning
confidence: 99%